The Diagnostic Usefulness of HMGA2, Survivin, CEACAM6, and SFN/14-3-3 δ in Follicular Thyroid Carcinoma - Jang, Min Hye; Jung, Kyeong Cheon; Min, Hye Sook (Journal of pathology and translational medicine, 2015)
Follicular thyroid carcinoma (FTC) is the second most common thyroid malignancy and its differential diagnosis includes follicular adenoma (FA) and adenomatous goiter (AG). Several ancillary markers have been suggested to aid in the diagnosis of FTC, but the successful use of these methods still needs to be validated. In the present study, we verified the immunoexpression of HMGA2, CEACAM6, survivin, and SFN/14-3-3 δ in lesions including 41 AGs, 72 FAs, and 79 FTCs. We evaluated their diagnostic usefulness, combined with galectin 3, Hector Battifora mesothelial 1 (HBME1), cytokeratin 19, and cyclin D1, in diagnosing FTC. The expressions of HBME1 (65.8%) and HMGA2 (55.7%) were significantly higher in FTCs than in FAs and AGs (p<.001 and p=.005, respectively). HBME1 was the only marker that was more frequently expressed in FTCs than in FAs (p=.021) and it was more frequently expressed in follicular neoplasms than in AGs (p<.001). Among the novel markers, the combination of HMGA2 and HBME1 showed the highest sensitivity (72.2%) and specificity (76.1%) for diagnosing FTC. CEACAM6, survivin, and SFN/14-3-3 δ were barely expressed in most cases. Our present results show that only HMGA2 can be beneficial in differentiating FTC using the novel markers.